Relativistic Wave Equation for Radiant Electron (2018)
In this article a relativistic wave equation for the accelerated radiant electron, indepen- dent of Dirac formalism, based on the concept of radiation of classical electrodynamics is proposed. This work describes the solution for the free electron case, the electromagnetic potentials, the invariance under Lorentz transformations, and an application to the atomic model and the conductor media.